2012
DOI: 10.1246/bcsj.20110256
|View full text |Cite
|
Sign up to set email alerts
|

Orbital Views on Electron-Transport Properties of Cyclophanes: Insight into Intermolecular Transport

Abstract: Electron-transport properties of cyclophanes are investigated with qualitative Hückel molecular orbital analysis for better understanding of the intermolecular interaction in molecular devices. Charge and electron transfers often take place via through-space interactions, which are observed both in large biological molecules and in organic molecular crystals. Since the intermolecular electronic coupling in ³-stacked structures plays an important role in total device performance, in this work [2,2]paracyclophan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(56 citation statements)
references
References 77 publications
5
51
0
Order By: Relevance
“…Along these lines, the [2.2]paracyclophane (PC) compound is highly appealing. 20 First described by Farthing et al in 1949, it consists of two stacked benzene rings that are mechanically stabilized by two nonconjugated linkers. 21 Integrated as central unit of an oligo-phenylene-ethynylene (OPE) rod with terminal binding groups to gold electrodes ( Figure 1 ), we show here that using a mechanically controlled break junction (MCBJ) the π-stacking (and, therefore, the conductance) can be modulated by exerting a mechanical shear force to it.…”
mentioning
confidence: 99%
“…Along these lines, the [2.2]paracyclophane (PC) compound is highly appealing. 20 First described by Farthing et al in 1949, it consists of two stacked benzene rings that are mechanically stabilized by two nonconjugated linkers. 21 Integrated as central unit of an oligo-phenylene-ethynylene (OPE) rod with terminal binding groups to gold electrodes ( Figure 1 ), we show here that using a mechanically controlled break junction (MCBJ) the π-stacking (and, therefore, the conductance) can be modulated by exerting a mechanical shear force to it.…”
mentioning
confidence: 99%
“…No essential differences in optical properties among the π-stacked molecules comprising pseudo– o –, – m –, and – p –linked [2.2]paracyclophanes were observed. It was reported that pseudo-m-linked [2.2]paracyclophane is symmetry-allowed for electron transport [28]. The present polymer can be a promising candidate to function as a single molecular wire that transfers electron effectively.…”
Section: Discussionmentioning
confidence: 93%
“…The quantum interference picture has emerged as a powerful tool in molecular conductance for relating the observed transmission through molecules bound between two gold electrodes to electronic structure, namely to molecular‐orbital considerations . The computational modeling by Solomon et al of benzene π‐stacks connected to gold electrodes would suggest higher transmission near the Fermi level for a pseudo ‐ meta than for a pseudo ‐ para arrangement, due to pronounced destructive interference effects for the latter.…”
Section: Resultsmentioning
confidence: 99%
“…The dependence of electronic coupling and conductance on the relative arrangements and spatial dislocations of the π‐systems and on the location of the points of connection to the locations of charge injection (redox centers or the leads in actual conduction experiments) is of central interest in this context. Such questions have recently been addressed by quantum‐chemical methods for unlinked π‐stacked benzene rings connected to electrode models, using either concepts based on quantum interference or on orbital‐symmetry‐based pictures . Nodes in the frontier orbitals lead to a strong influence of the connection points on the computed transmission near the Fermi level, but the latter also depends crucially on the charge‐injection energy …”
Section: Introductionmentioning
confidence: 99%